Analisis Kesalahan Siswa Berdasarkan Teori Kesalahan Kastolan dalam Menyelesaikan Soal Relasi dan Fungsi Kelas VIII SMP IT Bangkinang - Anisa, Uirma Isnani; Kartini, Kartini (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
Based on Kastolan's error theory, the mistakes made in solving math problems consist of three errors, namely conceptual, procedural, and technical. This study aims to analyze and explain the mistakes made by students when answering mathematical questions about relations and functions. This research is qualitative descriptive research. The subjects in this study were 30 class VIIIE students at SMP IT Bangkinang. Data collection is done by testing techniques. The instruments used were five questions of relations and functions in the form of descriptions. The validity of the questions was then calculated and the errors in the questions that met the categories used were analyzed. The results of the study showed that the most errors students made were procedural errors. The error rate of students based on the type of error is 12, 87% for conceptual errors, 74.26% for procedural errors, and 12.87% for arithmetic operations errors. Factors that make students make mistakes in working on relations and functions are that students do not pay attention, students cannot distinguish relations that are functions and not functions, and students are in a hurry to carry out algebraic operations, that students do not complete the problem until the final result.